Effects of temperature and meal size on the postprandial metabolic response of Leptodactylus latrans (Anura, Leptodactylidae) - Timpone, Lua T. [UNESP]; Gavira, Rodrigo S. B.; Andrade, Denis [UNESP] (Wiley-Blackwell, 2019)
The postprandial increment of metabolism, often referred to as specific dynamic action (SDA), encompasses the summed costs of meal ingestion, digestion, absorption, and assimilation. Different SDA parameters, such as its magnitude, duration, and relative cost, are affected by a diverse set of environmental and physiological determinants, including meal size and body temperature. While the influence of these variables has been thoroughly examined in most ectothermic vertebrate groups, few studies have focused on the determinants and consequences of the SDA response in anuran amphibians. Thus, we examined the effects of meal size and body temperature on the SDA response of a Neotropical frog, Leptodactylus latrans, by measuring the rates of oxygen consumption of frogs while fasting and after being fed meals of different sizes at different temperatures. SDA lasted from 3 to 5 days and increased with meal size for frogs fed meals equivalent to 5-15% of their body mass. SDA cost was not affected by meal size and averaged 14.6% of the caloric content of the meal. Temperature increment was accompanied by proportional increases in metabolic rate and shorter SDA duration. The relative SDA cost averaged 14.8% of the meal caloric content at 20 degrees C and 25 degrees C, but increased to 23.5% at 30 degrees C. Our results indicate that meal size imposes no physiological or energetic constraint to L. latrans feeding. Digestion at temperatures near the thermal preference of the species seems to optimize energetic return, whereas the shortening of SDA duration at higher temperatures may provide significant ecological advantages.
Keywords: anurans; digestion; energetics; meal size; postprandial metabolic increment; temperature